O papel da câmera na investigação do mundo vivo: uma análise da Trilogia Qatsi, de Godfrey Reggio - Maira Bueno Moura (2011)
The present study aims to conduct an analysis about Godfrey Reggios Qatsi Trilogy Koyaanisqatsi (USA, 1983), Powaqqatsi (USA, 1988) and Naqoyqatsi (USA, 2002). These are independent movies, which dont use the usual resources of film industry, such as dialogues its plot is based exclusively on imagery and music, and this study intends to analyze different theories of montage that are presented on Reggios movies. We sought to ascertain in what extent the construction of meaning in the Trilogy is obtained by the clash of images and if the Trilogys time is given by the speed of the cuts or by the internal rhythm of the plans.